Construction of Pickering Double Emulsions Based on Xanthan Gum/Lysozyme Nanoparticles: Structure, Stability, and Co-Encapsulation of Epigallocatechin Gallate and β-Carotene - Yongpeng Yin; Denglin Luo; Lala Li; Xingguo Li; Mengyao Kang; Bakht Ramin Shah; Xianling Wei; Wei Xu (Foods)
The low stability of water-in-oil-in-water (W1/O/W2) double emulsions greatly limits their applications. Therefore, in this study, W1/O/W2 Pickering double emulsions (PDEs) were prepared by a two-step emulsification method using polyglycerol polyricinoleate (PGPR) and xanthan gum/lysozyme nanoparticles (XG/Ly NPs) as lipophilic and hydrophilic emulsifiers, respectively. The regulation mechanism of the performance of PDEs by XG/Ly NPs was investigated, and the ability of the system to co-encapsulate epigallocatechin gallate (EGCG) and β-carotene was evaluated. The results showed that increasing the XG/Ly NPs concentration can enhance the stability of PDEs. At 60% W2 phase percentage and 2.0% XG/Ly NPs, the PDEs showed a smaller droplet size (23.47 ± 2.28 μm) and no phase separation after 21 days of storage. Additionally, the PDEs co-encapsulated system showed higher encapsulation efficiency (EGCG: 89.21%; β-carotene: 99.14%) and maintained high retention of active substances after 8 h of UV illumination (EGCG: 75.51%; β-carotene: 77.24%). As demonstrated by in vitro simulated gastrointestinal digestion assays, the bioaccessibility of EGCG and β-carotene simultaneously encapsulated was improved by 66.0% and 36.2%, respectively, compared with that of individually encapsulated EGCG and β-carotene. Overall, this study provides a new reference for the construction of highly stable PDEs and is promising as a co-encapsulation carrier for environmentally sensitive components.